2005
DOI: 10.1128/jvi.79.4.2420-2431.2005
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Human Herpesvirus 8/Kaposi's Sarcoma-Associated Herpesvirus Replication and Transcription Activator Transactivation by Interferon Regulatory Factor 7

Abstract: Human herpesvirus 8 (HHV-8)/Kaposi's sarcoma-associated herpesvirus infection goes through lytic and latent phases that are regulated by viral gene products, but very little is known about the involvement of host proteins. The replication and transcription activator (RTA) is a viral protein sufficient to initiate lytic replication by activating downstream genes, including the viral early gene open reading frame 57 (ORF 57), which codes for a posttranscriptional activator. In this study, we demonstrate that cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 54 publications
5
41
0
Order By: Relevance
“…42,50 In conclusion, our study demonstrating that HCV has the ability to undermine intracellular innate immunity of the host cells provides a plausible mechanism responsible for HCV persistence in the hepatic cells. Our data, in conjunction with the reports by Foy et al 3 and Wang et al, 39 suggest that HCV not only interferes with the IRF-3-mediated early protein pathway of type I IFNs, but also inhibits IRF-7-mediated IFN-␣ activation in the hepatic cells. Thus, HCV uses complex mechanisms to target multiple steps of the type I IFN signaling pathway in the hepatic cells, which results in significant suppression of endogenous IFN-␣, a critical self-defense weapon used by the hepatic cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…42,50 In conclusion, our study demonstrating that HCV has the ability to undermine intracellular innate immunity of the host cells provides a plausible mechanism responsible for HCV persistence in the hepatic cells. Our data, in conjunction with the reports by Foy et al 3 and Wang et al, 39 suggest that HCV not only interferes with the IRF-3-mediated early protein pathway of type I IFNs, but also inhibits IRF-7-mediated IFN-␣ activation in the hepatic cells. Thus, HCV uses complex mechanisms to target multiple steps of the type I IFN signaling pathway in the hepatic cells, which results in significant suppression of endogenous IFN-␣, a critical self-defense weapon used by the hepatic cells.…”
Section: Discussionsupporting
confidence: 89%
“…This speculation is supported by a recent report that IRF-7 can directly inhibit human herpesvirus 8 (HHV-8) replication. 39 These data support the possibility that other anti-HCV factor(s) induced by IRF-7 also play a role in the observed HCV replicon inhibition. These findings indicated that endogenous IFN-␣ indeed has a critical role in controlling HCV replication in the hepatic cells.…”
Section: Discussionsupporting
confidence: 69%
“…The 4th unit of the A/T repeat has also been shown to be part of a binding site for IRF7, which represses Rta transactivation of the Mta promoter (41).…”
Section: Resultsmentioning
confidence: 99%
“…A subset of these vIRFs are expressed during viral latency, suggesting that IFN-␣/␤ exerts antiviral effects on latent cells, thereby leading to selective pressure to maintain vIRF expression (9,31,65,102). Surprisingly, vIRF3 stimulates the transcriptional induction of the cellular IRF-7 (51), and KSHV maintains sequences in at least one key lytic promoter that binds cellular IRF-7, resulting in the inhibition of viral replication in the presence of an IFN-␣/␤ response (88). In addition, the promoter for the KSHV viral interleukin 6 (vIL-6) gene is transactivated by IFN-␣/␤, and its upregulation restores IL-6 autocrine growth signals lost when IFN-␣/␤ downregulates cellular IL-6 (13,63).…”
Section: Discussionmentioning
confidence: 99%